Biological Pacemaker - Das, Uzzal Kanti; Ahsan, Syed Ali; Patwary, Mohammad Saifullah; Haque, KMHS Sirajul; Zaman, SM Mustafa; Hoque, Md Harisul (University Heart Journal, 2011)
Electronic cardiac pacemakers are the definitive treatment of sinoatrial node (SAN) dysfunction and high degree atrioventricular block. But they have limitations like limited battery life, need for lead implantation into heart and lack of response to autonomic and physiologic demands on the heart. Genetically engineered biological pacemakers could be a possible alternative to electronic pacemakers. The strategies include upregulation of β-1 adrenergic receptors, conversion of cardiomyocyte into pacemaker cells and stem cell therapy. Investigators created biological pacemakers in animal models by gene therapy targeting If current (HCN) and inward rectifier current (IkI) (Kir 2.1). They delivered pacemaker current gene into animal heart by using viral vectors and human mesenchymal stem cells (hMSC). The limitations noted are longevity and stability of pacemaker genes and the chance of migration and tumour formation after stem cells therapy. Key words: Sinoatrial node (SAN); HCN-2 gene; If current; inward rectifier current (Ikl); human embryonic stem cells. DOI: 10.3329/uhj.v6i1.7189 University Heart Journal Vol.6(1) 2010 pp.35-36